Effect of position - Trendelenburg and horizontal on the height of sensory block in patients undergoing lower abdominal surgery - Sarmila Guha Banerjee,; Shantanu Hazra,; Akashleena Banerjee,; Ujjwal Bandyopadhyay, (Asian Journal of Medical Sciences, 2023)
Background: Subarachnoid anesthesia also known as spinal anesthesia is now considered to be a safe form of anesthesia for lower abdominal and lower limb surgeries. The height of sensory block achieved in spinal anesthesia after drug administration can be altered by changing the position of the patient, and this precisely is the advantage of using hyperbaric local anesthetic drug. Aims and Objectives: The aim of this study is to compare the effect of position – horizontal and Trendelenburg on the height of sensory block in spinal anesthesia. Materials and Methods: After obtaining the institutional ethical clearance, total 66 patients scheduled for lower abdominal surgery under spinal anesthesia were selected and divided into two groups – Group A patients were placed in Trendelenburg position with 20° head down for 40 s and then returned to horizontal position and Group B patients were placed in horizontal position after spinal anesthesia. The level of sensory block was compared among the two groups at different points of time up to 30 min of drug administration. Results: The patients who remained in Trendelenburg position for 40 s after spinal anesthesia achieved a higher level of sensory block earlier as compared to the horizontal group and the maximum block height was two spinal segments higher than that of the horizontal group. Conclusion: From our current study, we can conclude that Trendelenburg position can be used to achieve a higher level of sensory block as compared to horizontal position after successful neuraxial block.